Influence of Nepal’s Foreign Policy on Domestic Political Dynamics - Aswasthama Bhakta Kharel (Interdisciplinary Journal of Management and Social Sciences, 2024)
This research explores the impact of Nepal’s foreign policy on its domestic politics, analyzing how international relations shape internal political dynamics. Through a thorough examination of secondary sources, the study investigates key elements such as economic aid, trade agreements, military cooperation, and diplomatic relations with major global and regional powers. The findings reveal that Nepal’s strategic location between India and China significantly affects its domestic political landscape, influencing political alliances and public opinion. Specifically, economic aid and foreign investments have a direct impact on domestic policy decisions, while international trade agreements affect local economic stability and political attitudes. Additionally, the role of the Nepalese diaspora and labor migration agreements reflects the complex relation between foreign policy and domestic labor markets. The research analyzes the importance of a balanced and nuanced foreign policy that addresses both geopolitical pressures and domestic needs to maintain political stability and foster development in Nepal. It recommends enhancing transparency in foreign policy decisions and increasing public engagement to reduce negative domestic impacts and promote a more inclusive political environment.